2016
DOI: 10.1302/0301-620x.98b12.37568
|View full text |Cite
|
Sign up to set email alerts
|

Myxofibrosarcoma of the extremity and trunk

Abstract: High rates of positive margins and the need for further excision makes this tumour particularly suited to management by multidisciplinary surgical teams. Microscopic tumour can be present up to 29 mm from the macroscopic tumour in fascially-based tumours. Cite this article: Bone Joint J 2016;98-B:1682-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
1
25
1
Order By: Relevance
“…Previous imaging studies have shown that MFS has a tendency to grow in so-called ''tail sign" curvilinear extensions that arise from the main tumor 12,13 . These extensions are thought to correlate with microscopic spread of the tumor along fascial planes and have been found extending up to 3 centimeters away from macroscopically visible tumor borders 12,14,15 . Unfortunately, intraoperatieve delineation of these tumor borders and extensions…”
mentioning
confidence: 99%
“…Previous imaging studies have shown that MFS has a tendency to grow in so-called ''tail sign" curvilinear extensions that arise from the main tumor 12,13 . These extensions are thought to correlate with microscopic spread of the tumor along fascial planes and have been found extending up to 3 centimeters away from macroscopically visible tumor borders 12,14,15 . Unfortunately, intraoperatieve delineation of these tumor borders and extensions…”
mentioning
confidence: 99%
“…On the other hand, the lesion warranted further investigation, ideally with X-ray and MRI imaging. The biopsy should be a core needle biopsy, conducted in a reference center and evaluated by a specialized pathologist rather than in a referring institution, since in the latter a higher error rate has been detected, possibly related to the heterogeneous nature of the histology of MFS, which can lead to misdiagnosis [11,12,15]. In our patient, the preoperative biopsy was an incisional biopsy, interpreted by a general pathologist, in a referring center.…”
Section: Discussionmentioning
confidence: 98%
“…Normally MFS presents as a gradually enlarging, painless mass in soft tissues or bone, causing occasionally pain, paresthesia and edema. They frequently appear in the extremities [11,12]. Given their rarity, they may be confused with lipomas, cysts, panniculitis or osteochondral lesions [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations